Unmet Prenatal Expectations During the COVID-19 Pandemic. Issue 2 (March 2022) - Goyal, Deepika; Rosa, Liana De La; Mittal, Leena; Erdei, Carmina; Liu, Cindy H.
Abstract: Purpose: To explore the experiences of pregnant women who were living in the United States during the COVID-19 pandemic. Study Design and Methods: Using a qualitative design, we used data obtained from women in their second or third trimester of pregnancy who participated in the Perinatal Experiences and COVID-19 Effects (PEACE) Study from May 21 to December 22, 2020. Results: 361 of 408 pregnant women (88%) who participated in the PEACE study during that timeframe provided narrative comments. Participants had a mean age of 33.2 years (SD = 3.7) with a high percentage of White women (91.4%). At the time of participation, women were between 2.4 and 8.6 months into the COVID-19 pandemic. Just under half were pregnant for the first time ( n = 177). Content analysis of responses revealed an overall sense of "unmet expectations" within two themes involving the role of relationships: 1) losing the experience of going through pregnancy together and 2) loss of social support and expected relationship building . Differences were noted between participants giving birth for the first time and participants with other children at home. Clinical Implications: This study offers insight for nurses and other clinicians taking care of pregnant women during times of public health crises and provides implications for the care of women as the pandemic continues. Nurses can help women plan for future health care changes that may disrupt their support needs as seen during the COVID-19 pandemic. Nurses should also be aware of possible enduring effects of prenatal unmet needs on later outcomes. Abstract : Restrictions initiated by birthing hospitals and prenatal care providers significantly changed traditional routines for care during pregnancy to minimize risk of exposure to COVID-19 for pregnant women and their care givers. Many women attended prenatal visits alone and were unable to share the usual pregnancy milestones with their partners. In this study, women describe their unmet expectations for pregnancy in the context of these changes during the COVID-19 pandemic.